Gambaran kepatuhan terapi antiretroviral pada lelaki-seks-lelaki di Klinik Bali Medika - Phebe Indriani; Putu Cintya Denny Yuliyatni; Luh Seri Ani; I Wayan Weta (DiscoverSys Inc., 2020)
Background: HIV prevalence in Indonesia and Bali is quite large. The main factor in achieving success in the treatment of HIV / AIDS virus infections is compliance.Aim: This study aims to determine the adherence of ARV therapy to MSM based on the characteristics and clinical stage in one of the CST clinics, the Bali Medika clinic. This descriptive study with cross sectional design used simple random sampling from the register of HIV patients at the Bali Medika Clinic so as to get 90 MSM (male-sex-male) patients. Data sources were taken from medical records regarding the characteristics, clinical stage, and treatment compliance of the study subjects. The data obtained were analyzed and displayed in the form of frequency tables and cross tables.Results: The majority of MSM sufferers with HIV are less than 31 years old; single (95.6%); low education (52.2%); have a job (94.4%); are in clinical stage I (77.8%); do not have coinfection (86.7%); use FDC drugs (92.2%); and suffered side effects from dizziness (90.0%). Most (66.7%) adhere to the Bali Medika Clinic.Conclusion: MSM at the Bali Medika Clinic tend to have high compliance in carrying out ARV therapy.Â Latar Belakang: Prevalensi HIV di Indonesia dan Bali cukup besar. Faktor utama dalam mencapai keberhasilan pengobatan infeksi virus HIV/AIDS adalah kepatuhan.Tujuan: Penelitian ini bertujuan untuk mengetahui kepatuhan terapi ARV pada LSL (lelaki-seks-lekali) berdasarkan karakteristik dan stadium klinis di salah satu klinik CST, yaitu klinik Bali Medika.Metode: Desain penelitian dengan rancangan potong lintang ini menggunakan simple random sampling dari daftar register pasien HIV di Klinik Bali Medika sehingga mendapatkan 90 pasien LSL. Sumber data diambil dari rekam medis mengenai karakteristik, stadium klinis, dan kepatuhan terapi dari subjek penelitian. Data yang diperoleh dianalisis dan ditampilkan dalam bentuk tabel frekuensi dan tabel silang.Hasil: Sebagian besar LSL penderita HIV berusia kurang dari sama dengan 31Â tahun; belum menikah (95,6%); berpendidikan rendahÂ (52,2%); memiliki pekerjaan (94,4%); berada dalam stadium klinis I (77,8%); tidak memiliki koinfeksi (86,7%); menggunakan jenis obat FDC (92,2%); dan menderita efek samping pusing (90,0%). Sebagian besar (66,7%) patuh berkunjung ke Klinik Bali Medika.Simpulan: LSL di Klinik Bali Medika cenderung memiliki kepatuhan yang tinggi dalam menjalankan terapi ARV.